An examination of socioeconomic and racial/ethnic disparities in the awareness, knowledge and utilization of three colorectal cancer screening modalities. (June 2021) - Zhu, Xuan; Parks, Philip D.; Weiser, Emily; Griffin, Joan M.; Limburg, Paul J.; Finney Rutten, Lila J.
Abstract: While colorectal cancer (CRC) mortality rates have been decreasing, disparities by socioeconomic status (SES) and race/ethnicity persist. CRC screening rates remain suboptimal among low SES and racial/ethnic minority populations, despite the availability of multiple screening modalities. Understanding awareness, knowledge, and utilization of common screening modalities within different racial/ethnic and SES groups is critical to inform efforts to improve population screening uptake and reduce disparities in CRC-related health outcomes. Through the theoretical lenses of diffusion of innovation and fundamental cause theory, we examined the associations of race/ethnicity and SES with awareness, knowledge, and utilization of three guideline recommended CRC screening strategies among individuals at average risk for CRC. Data were obtained from a survey of a nationally representative panel of US adults conducted in November 2019. The survey was completed by 31.3% of invited panelists (1595 of 5097). Analyses were focused on individuals at average risk for CRC, aged 45–75 for awareness and knowledge outcomes (n = 1062) and aged 50–75 for utilization outcomes (n = 858). Analyses revealed racial/ethnic and SES disparities among the three CRC screening modalities, with more racial/ethnic and SES differences observed in the awareness, knowledge, and utilization of screening colonoscopy and mt-sDNA than FIT/gFOBT. Patterns of disparities are consistent with previous research showing that inequities in social and economic resources are associated with an imbalanced adoption of medical innovations. Our findings demonstrate a need to increase awareness, knowledge, and access of various CRC screening modalities in specific populations defined by race/ethnicity or SES indicators. Efforts to increase CRC screening should be tailored to the needs and social-cultural context of populations. Interventions addressing inequalities in social and economic resources are also needed to achieve more equitable adoption of CRC screening modalities and reduce disparities in CRC-related health outcomes. Highlights: Socioeconomic status linked to screening method awareness gap, notably mt-sDNA. Screening modalities with low demand on patient resources more likely to be adopted. Screening education needs to emphasize uniform starting age for all modalities. Tailoring education to low resource communities may improve screening uptake.